An Analysis of the Promotional Strategy at RSIA Fadhila Batusangkar - Nerissa, Nidianti; Yeni, Yulia Hendri; Putra, Abdi Setya (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: According to the 2016 Indonesia Health Profile, the quantity of hospitals in Indonesia experienced growth between 2013 and 2016. The quantity of hospitals witnessed a rise from 2,228 in 2013 to 2,601 in 2016. As of 2016, Indonesia had a total of 555 Special Hospitals and 2,046 General Hospitals operating within its hospital system. Hospitals in Indonesia undoubtedly face fierce competition; consequently, it is not illogical for hospital administrators to consider marketing strategies in an effort to overcome the obstacles that already exist.Method: The research employed a qualitative methodology, encompassing in-depth interviews, document analysis, and observations conducted at RSIA Fadhila Batusangkar. By employing the triangulation technique and conducting content analysis and data validation, conclusions will be reached.Result: The study's findings indicate that each component of the marketing communication combination yields distinct outcomes. There are low, medium, and high impacts of each of the eight elements on the enthusiasm of the target market. Additionally, the issues that are present in each element are distinct. Every aspect is beset with challenges, commencing with subpar human resources that lacks development and training, supporting facilities for mobilization, and materials for producing promotional content; the dissemination of promotional media continues to be limited in scope and lacks a comprehensive evaluation system; and so forth. The hospital must implement both short-term and long-term solutions, including enhancing its human resources and implementing promotional support recommendations.